PRODUKTIVITAS USAHATANI PADI GOGO PADA LAHAN BEKAS TEBANGAN HUTAN JATI (Tectona grandis L.) (Productivity of Upland Rice Farming on Logged Over Area of Teak Forest (Tectona grandis L.)) - Darsono Priono; Suhartono Suhartono (Balai Litbang Teknologi Agroforestry, Ciamis, 2020)
Upland rice has been cultivated by intercropping patterns on the logged area of the teak forest in Java Island for a long time. However, the activities of upland rice farming are still subsistence and not profit-oriented. This study aims to determine the feasibility of upland rice farming on the logged area of teak forests based on farming productivity. Data was collected using a survey and interview to 30 farmers who cultivated upland rice on the logged area of Perhutani teak forest. To find out the productivity of upland rice farming, an analysis on land productivity, labor productivity, and capital productivity was carried out. The results showed that the upland rice farming on the logged area of teak forest feasible to do with land productivity of IDR 579,028 per 0.24 ha, labor productivity of IDR 55,200 per day and capital productivity of 17.13%.